Pengaruh Komisaris Independen, Kepemilikan Institusional, Profitabilitas, dan Audit Tenure Pada Ketepatwaktuan Publikasi Laporan Keuangan Tahunan - Putri, Lita Leonie Tirta; Asmara Putra, I Nyoman Wijana (E-Jurnal Akuntansi, 2018)
ABSTRACT The information in the financial statements is considered relevant when delivered on time that will affect economic decision-making. The purpose of this research is to analyze factors that affect the timeliness of the publication of the financial statements of banking companies . Factors studied in this research are independent commissioners, institutional owneship, profitability, and audit tenure as independent variables while the timeliness as a dependent variable. The population in this research are all banking companies listed on the Indonesia Stock Exchange period 2012-2016. Determination method of sample in this research is non-participant method with purposive sampling technique. The number of samples in this research are 97 financial statements of banking companies listed on the Stock Exchange during the period 2012-2016. The analysis technique used in this research is logistic regression. Based on the results of the analysis it is known that the audit tenure has an effect on the timeliness of the publication of annual financial statements. Independent commissioners, institutional ownership, and profitability have no effect on the timeliness of the publication of the annual financial statements. Keywords : Independent commissioners, institutional ownership, profitability, audit tenure,          and timeliness of the publication of the annual financial statements